State Capacities in Innovation and Regulation in Regenerative Medicine in the United States of America - Acero, Liliana (British Journal of Healthcare and Medical Research, 2023)
Regenerative medicine has transformed medical practices, focusing upon the repair and regeneration of cells, tissues and genes. However, there are still contradictions in regulation that require the development of new State capacities and public debates on collective health. The present article is innovative theoretically and empirically as it analyzes how these State capacities have developed in the USA, a world leader in the area. It describes the conflicts and lacunae involved in that process, as part of a wider comparative research project. Methodologically, it is based upon a qualitative bibliographical and documentary analysis of official documents and secondary data. It discusses the different phases of American Federal regulations on regenerative medicine, exemplifies with the role of a State-level research center and illustrates how the lack of adequate regulation has contributed to the growth of uncertified clinics, genetic diagnoses and therapies, often detrimental to collective health. The main findings of the paper are the existence of a lack of coordination and/or conflict between policies on regenerative medicine at the State and Federal levels, the challenges faced on the integration of the private industrial sector and on business models for the reimbursement of expenses to stakeholders, as well as, on ways of lowering the high prices of present therapies and simplifying bureaucratic procedures for their approval. It emphasizes future challenges in the area that will probably also affect Brazil.